Space Pattern of Samudera Pasai Sultanate - Mirsa, Rinaldi; Muhammad, Muhammad; Saputra, Eri; Farhana, Izzati (International Journal of Engineering, Science and Information Technology, 2021)
Samudera Pasai is one of the Islamic Sultanates in Indonesia which appeared in the Middle Ages or around 1267 AD. Evidence of the existence of the Sultanate of Samuedra Pasai in Indonesia is listed in the book Rihlah ilal-Masyriq (Wanderings to the East) written by Abu Abdullah Ibnu Batutha (1304 - 1368 AD), a Muslim adventurer who traveled to Samudera Pasai in 1345 AD. The spatial pattern of the Samudera Pasai Sultanate is no longer visible because there are no traces of archaeological remains in the form of any remaining buildings, except for the tombs of Sultanate figures and historical records of foreign adventurers who have explored the Samudera Pasai Sultanate. This record strengthens the evidence of the existence of the Samudera Pasai Sultanate. The methodology used in this case is a phenomenological approach and a historical approach, which are expected to approach optimal results in uncovering spatial patterns in the development of Islam. The spatial arrangement of the sultanate generally used the concept of catur gatra tungga, which was arranged in the form of: alun-alun (the square) as the center of space, markets to the north of the square, palaces to the south of the square, and mosques to the west of the square. The spatial arrangement then formed a spatial pattern that became the center of the Samudera Pasai Sultanate.